2000
DOI: 10.1128/mmbr.64.3.515-547.2000
|View full text |Cite
|
Sign up to set email alerts
|

Signal Peptide-Dependent Protein Transport in Bacillus subtilis : a Genome-Based Survey of the Secretome

Abstract: SUMMARY One of the most salient features of Bacillus subtilis and related bacilli is their natural capacity to secrete a variety of proteins into their environment, frequently to high concentrations. This has led to the commercial exploitation of bacilli as major “cell factories” for secreted enzymes. The recent sequencing of the genome of B. subtilis has provided major new impulse for analysis of the molecular mechanisms underlying protein secretion by this organism. Most importantly, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
778
1
10

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 747 publications
(800 citation statements)
references
References 340 publications
(341 reference statements)
11
778
1
10
Order By: Relevance
“…Since from the SignalP algorithm it is predicted that CwlK seems to have a secretory signal peptide, it is possible that CwlK is secreted and localized outside of the cell. On the other hand, because it is also predicted that this protein seems to have a lipoprotein signal peptide described by Tjalsma et al (2000), CwlK may be localized in membrane as a lipoprotein. In order to clarify the role of CwlK, we determined the localization of CwlK with YCDDd (cwlK::erm) and the wild-type strain during the vegetative growth phase by SDS-PAGE and zymography.…”
Section: Determination Of the Cleavage Site In Peptidoglycan For H-∆cwlkmentioning
confidence: 99%
See 1 more Smart Citation
“…Since from the SignalP algorithm it is predicted that CwlK seems to have a secretory signal peptide, it is possible that CwlK is secreted and localized outside of the cell. On the other hand, because it is also predicted that this protein seems to have a lipoprotein signal peptide described by Tjalsma et al (2000), CwlK may be localized in membrane as a lipoprotein. In order to clarify the role of CwlK, we determined the localization of CwlK with YCDDd (cwlK::erm) and the wild-type strain during the vegetative growth phase by SDS-PAGE and zymography.…”
Section: Determination Of the Cleavage Site In Peptidoglycan For H-∆cwlkmentioning
confidence: 99%
“…The cwlK gene encodes a polypeptide consisting of 167 amino acid residues and its N-terminal region contains a signal sequence based on the SignalP (http://www.cbs.dtu.dk/services/SignalP/) algorithm, and the signal sequence is predicted to be MNLPAKTFVILCILFLLDLCFSYIRH 26 ↓E 27 (the arrow indicates the cleavage point and the numbers are with respect to the N-terminal amino acid residue). Tjalsma et al (2000) also described that the signal sequence of CwlK is assumed to be The wild-type B. subtilis is rod-shaped, and exists as short chains in the vegetative growth phase and as short rods in the stationary phase. Several previous reports indicated that autolysins in B. subtilis can induce lysis, and play roles in cell separation, cell elongation, motility, cell wall turnover, etc.…”
Section: Determination Of the Cleavage Sites Of Cell Wall Peptidoglycanmentioning
confidence: 99%
“…One particular phylum alone, the Proteobacteria, made the further addition of the SecB chaperone to reduce the problem of denaturation and degradation of proteins prior to secretion. I suggest that this problem became particularly acute in actinobacteria, which are often thermophiles (never hyperthermophiles) that secrete an unusually large number of proteins or peptides ; pronounced protein secretion is a basic characteristic of posibacteria -Bacillus subtilis secretes over 300 (Tjalsma et al, 2000) ; its more-complex SRP has helices 1-4 like neomura. These two features of their lifestyle may explain why the ancestral actinobacterium evolved proteasomes for the degradation of misfolded or denatured proteins.…”
Section: Derived Neomuran Protein-secretion and -Glycosylation Mechanmentioning
confidence: 99%
“…not all, secretory proteins follow this post-translational pathway. In Bacillus subtilis (and, very likely, other posibacteria), however, only a minority of secretory enzymes use the SecA post-translational mechanism ; the great majority are probably secreted co-translationally by the SRP mechanism (Tjalsma et al, 2000). Neomura, however, do not have SecA and secrete essentially all proteins with a cleavable signal sequence co-translationally.…”
mentioning
confidence: 99%
“…The C. perfringens ␤-toxoid native signal sequence is a consensus Sec-type signal sequence, and in theory compatible with the B. subtilis secretion system (Tjalsma et al, 2000). Swapping the ␤-toxoid signal sequence with the signal sequence of a well secreted Bacillus protein (AmyQ) did not increase its presence in the growth medium.…”
Section: Secretion Signalsmentioning
confidence: 98%